The Analisis Korelasi dan Sidik Lintas Karakter Pertumbuhan dan Komponen Hasil terhadap Hasil Bawang Merah (Alllium Cepa L. Var Aggregatum) di Dataran Tinggi: Analisis Korelasi dan Sidik Lintas Karakter Pertumbuhan dan Komponen Hasil terhadap Hasil Bawang Merah (Alllium Cepa L. Var Aggregatum) di Dataran Tinggi - Nurmalita Waluyo; Noladhi Wicaksana; Anas Anas; Ineu Sulastrini; Joko Pinilih; Iteu M. Hidayat (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Shallot commodity is a strategic commodity and has high economic value and cannot be substituted for other commodities. This research aimed to observe the correlation, direct and indirect effect between growth and yield components characters to shallot yield in the highlands. This experiment was conducted from September to November 2019 in Lembang (West Bandung Regency), Pacet (Bandung Regency), and Samarang (Garut Regency). The research material included 12 shallot genotypes, namely B1 clone, B19 clone, B63 clone, B72 clone, B77 clone, B102 clone, B222 clone, Trisula, Bali Karet, Maja Cipanas, Bima Brebes, and Sumenep. The experiment was arrange in Randomized Block Design (RBD), with 3 (three) replication. The results of the correlation analysis showed that there was a very significant positive correlation between the character of leaf length, and wet bulb weight per clump to wet bulb yields per hectare in all test locations. Leaf length is a character that has a very significant positive correlation and has a very high positive direct effect on the yield of wet bulb  per hectare in all test locations in the highlands. Selection of shallots to increase the yield of wet bulb per hectare in the highlands can be done directly through the growth character, namely leaf length.